HYBRID TECHNOLOGY–A NEW VISTA IN PIGEONPEA BREEDING - K. B. SAXENA, ANUPAMA HINGANE, C. SUDHAKAR, S.N.V.C.L. PUSHPAVALLI, K.N. YAMINI, C.V. SAMEER KUMAR, SUHAS P WANI, M.V. NAGESH KUMAR, P. JAGANMOHAN RAO (The Journal of Research, PJTSAU, 2019)
Once designated as an ‘orphan crop’ to now being crowned as a mainstream ‘commercial crop’, pigeonpea has evolved over the decades as lifeline for millions of resource poor farmers in the semi-arid tropics, where it is cultivated for both subsistence and commercial purpose.Pigeonpea [Cajanus cajan (L.)] is the sixth most important legume crop, grown predominantly in the tropical and sub-tropical regions of Asia, Africa and Latin America. India is considered as the center of origin of pigeonpea (Van der Maesen, 1980) because of its natural genetic variability available in the local germplasm and the presence of its wild relatives in the country.